Acetylcholine ameliorated TNF-α-induced primary trophoblast malfunction via muscarinic receptors. Issue 6 (9th September 2020) - Wang, Zheng; Zibrila, Adoulaye Issotina; Liu, Shuhua; Zhao, Gongxiao; Li, Yubei; Xu, Jingning; Liu, Dan; Li, Chunfang; Feng, Weiyi; Liu, Jinjun
Abstract: Oxidative stress and apoptosis of trophoblasts are involved in preeclampsia (PE). Numerous studies have shown that acetylcholine (ACh), the principal vagal neurotransmitter, plays a crucial role in attenuating oxidative stress, inflammation, and apoptosis in a variety of human diseases. However, the role of ACh in PE management remains unclear. Here, we aimed to determine the effects of ACh on TNF-α-treated human primary trophoblast cells. Western blotting, CCK-8, DHE, TUNEL immunofluorescence staining, transwell assays, and wound-healing assays were performed to evaluate the role of ACh in vitro. We found that both TNF-α expression and the apoptotic index were higher in placentas from preeclamptic women than in normal placentas. TNF-α enhanced oxidative stress and increased the number of TUNEL-positive nuclei, Bax/Bcl-2 ratio, and the cleaved caspase-3/caspase-3 ratio while decreasing cell viability in primary human trophoblast cells. TNF-α promoted cell migration and invasion. PDTC, a selective NF-κB inhibitor, significantly blunted TNF-α-induced effects. ACh treatment attenuated oxidative stress and apoptosis while further promoting migration and invasion of TNF-α-treated primary trophoblast cells. The effects of ACh could be reversed by the muscarinic receptor antagonist atropine. Overall, our findings indicate that ACh significantly ameliorates TNF-α-induced oxidative stress and apoptosis of human primary trophoblast cells via muscarinic receptors. This is the first time that the improvement of vagal activity served as a therapeutic strategy for PE-like trophoblasts, suggesting its potential value in clinical practice. Abstract : Summary Sentence TNF-α is increased in the placentas from preeclamptic women and acetylcholine significantly ameliorates TNF-α-induced oxidative stress and apoptosis of human primary trophoblast cells via muscarinic receptors.